Analysis of the human env-specific cytotoxic T-lymphocyte (CTL) response in natural human immunodeficiency virus type 1 infection: low prevalence of broadly cross-reactive env-specific CTL. - Carmichael, A (1996)
Major histocompatibility complex-restricted cytotoxic T lymphocytes (CTL) are part of the cellular immune response to persistent virus infections. Candidate vaccines against human immunodeficiency virus type 1 (HIV-1) should elicit broad cross-reactive immunity to confer protection against different strains of HIV-1. As it is likely that candidate vaccines will include the envelope gene product Env, we determined the proportion of CTL clones which recognized variable and conserved determinants in three env variants during natural infection. Limiting dilution analysis was used to characterize numerous short-term CTL clones derived from peripheral blood of HIV-1-infected subjects, using split-well analysis to assay cytotoxicity against target cells expressing gp160env of HIV-1 strains IIIB, MN, and RF. In 9 of 12 HIV-1-infected subjects, at the clonal level most env-specific CTL recognized determinant(s) within one env variant but not in the other variants. In some subjects, CTL recognized multiple nonconserved determinants in different variants. The pattern of recognition of different env variants was relatively stable over time. In most of the patients studied, the proportion of CTL which showed cross-recognition of conserved determinants shared among the three strains was low. Two novel CTL epitopes within gp41 were identified by using 15-mer peptides of the HIV-SF2 sequence. When specific peptide was used to stimulate CTL precursors in vitro, the frequency of peptide-specific CTL precursors was very high, but the CTL elicited by this stimulation were highly strain specific. We conclude that the use of a single HIV env variant to detect CTL activity can underestimate the magnitude and complexity of the env-specific CTL response. The low prevalence of CTL clones which show cross-recognition of conserved determinants may have implications for immunization strategies based solely on env; to elicit broadly cross-reactive CTL other, more conserved viral antigens are likely to be needed in addition to env. Because of its capacity to distinguish CTL responses against different virus strains, limiting dilution analysis is particularly appropriate to quantitate the immune responses generated by candidate env-based vaccines.